Immunomodulatory Drug CC-4047 is a Cell-type and Stimulus-Selective Transcriptional Inhibitor of Cyclooxygenase 2 - Ferguson, Gregory D.; Jensen-Pergakes, Kristen; Wilkey, Candice; Jhaveri, Urvi; Richard, Normand; Verhelle, Dominique; De Parseval, Laure Moutouh; Corral, Laura G.; Xie, Weilin; Morris, Christopher L.; Brady, Helen; Chan, Kyle (Journal of Clinical Immunology, 2007)
COX2 (prostaglandin G/H synthase, PTGS2) is a well-validated target in the fields of both oncology and inflammation. Despite their significant toxicity profile, non-steroidal anti-inflammatory drugs (NSAIDs) have become standard of care in the treatment of many COX2-mediated inflammatory conditions. In this report, we show that one IMiDs((R)) immunomodulatory drug, CC-4047, can reduce the levels of COX2 and the production of prostaglandins (PG) in human LPS-stimulated monocytes. The inhibition of COX2 by CC-4047 occurs at the level of gene transcription, by reducing the LPS-stimulated transcriptional activity at the COX2 gene. Because it is a transcriptional rather than an enzymatic inhibitor of COX2, CC-4047 inhibition of PG production is not susceptible to competition by exogenous arachadonic acid (AA). The distinct mechanisms of action allow CC-4047 and a COX2-selective NSAID to work additively to block PG secretion from monocytes. CC-4047 does not, however, block COX2 induction in or prostacyclin secretion from IL-1beta stimulated human umbilical vein endothelial cells (HUVEC) cells, nor does it inhibit COX1 in either monocytes or HUVEC cells. CC-4047 also inhibits COX2 and PG production in monocytes derived from patients with sickle cell disease (SCD). Taken together, the data in this manuscript suggest CC-4047 will provide important anti-inflammatory benefit to patients and will improve the safety of NSAIDs in the treatment of SCD or other inflammatory conditions.